Origin of worldwide cultivated barley revealed by NAM-1 gene and grain protein content - Wang, Yonggang; Ren, Xifeng; Sun, Dongfa; Sun, Genlou (Frontiers in Plant Science, 2015)
The origin, evolution and distribution of cultivated barley provides powerful insights into the historic origin and early spread of agrarian culture. Here, population-based genetic diversity and phylogenetic analyses were performed to determine the evolution and origin of barley and how domestication and subsequent introgression have affected the genetic diversity and changes in cultivated barley on a worldwide scale. A set of worldwide cultivated and wild barleys from Asia and Tibet of China were analyzed using the sequences for NAM-1 gene and gene-associated traits-GPC (grain protein content). Our results showed Tibetan wild barley distinctly diverged from Near Eastern barley, and confirmed that Tibet is one of the origin and domestication centers for cultivated barley, and in turn supported a polyphyletic origin of domesticated barley. Comparison of haplotype composition among geographic regions revealed gene flow between Eastern and Western barley populations, suggesting that the Silk Road might have played a crucial role in the spread of genes. The GPC in the 118 cultivated and 93 wild barley accessions ranged from 6.73% to 12.35% with a mean of 9.43%. Overall, wild barley had higher averaged GPC (10.44%) than cultivated barley. Two unique haplotypes (Hap2 and Hap7) caused by a base mutations (at position 544) in the coding region of the NAM-1 gene might have a significant impact on the GPC. SNPs and haplotypes of NAM-1 associated with GPC in barley could provide a useful method for screening GPC in barley germplasm. The Tibetan wild accessions with lower GPC could be useful for malt barley breeding